Cep295 is a conserved scaffold protein required for generation of a bona fide mother centriole - Yuki Tsuchiya (Nature Communications, 2016)
Newly formed centrioles mature into functional mother centrioles. Here the authors show that the scaffolding protein Cep295 is recruited to the procentriole assembly site and assists daughter centriole assembly and daughter-to-mother centriole conversion.